Education and nutrition intervention to mitigate stunting in Cisaranten Wetan, Cinambo District, Bandung - Dewi Astriany; Adang Firmansyah; Pupung Ismayadi; Iffa Risfayanti; Rizki Amaludin Mutaqin; Sani Nurlaela Fitriansyah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Stunting is a complex problem related to environmental health and the provision of nutritious food. Chronic malnutrition in children results in permanently impaired physical and cognitive growth. Cisaranten Wetan Village, Cinambo District, Bandung has problems with the health conditions of children who are indicated to be stunted. The purpose of this service activity is to provide education to Integrated Healthcare Center (in Indonesia: Posyandu) cadres and the community regarding stunting, as well as assistance with specific nutritional interventions for children indicated as stunted. Education was conducted by the STFI Community Service Team with the theme of balanced nutrition and child development in the form of counseling, videos, and leaflets. Children who are indicated to be stunted are given additional food in the form of egg powder, curcumin honey, and goat milk regularly. The existence of routine education carried out with various media causes a change in the level of knowledge from the moderate category to good in mother respondents with children who are indicated to be stunted. Increased maternal knowledge affects behaviour in parenting and child growth and development.